The predicted impact and cost‐effectiveness of systematic testing of people with incident colorectal cancer for Lynch syndrome. Issue 2 (8th October 2019) - Kang, Yoon‐Jung; Killen, James; Caruana, Michael; Simms, Kate; Taylor, Natalie; Frayling, Ian M; Snowsill, Tristan; Huxley, Nicola; Coupe, Veerle MH; Hughes, Suzanne; Freeman, Victoria; Boussioutas, Alex; et al.
Abstract: Objectives: To evaluate the health impact and cost‐effectiveness of systematic testing for Lynch syndrome (LS) in people with incident colorectal cancer (CRC) in Australia. Design, setting, participants: We investigated the impact of LS testing strategies in a micro‐simulation model ( Policy1–Lynch ), explicitly modelling the cost of testing all patients diagnosed with incident CRC during 2017, with detailed modelling of outcomes for patients identified as LS carriers (probands) and their at‐risk relatives throughout their lifetimes. For people with confirmed LS, we modelled ongoing colonoscopic surveillance. Main outcome measures: Cost‐effectiveness of six universal tumour testing strategies (testing for DNA mismatch repair deficiencies) and of universal germline gene panel testing of patients with incident CRC; impact on cost‐effectiveness of restricting testing by age at CRC diagnosis (all ages, under 50/60/70 years) and of colonoscopic surveillance interval (one, two years). Results: The cost‐effectiveness ratio of universal tumour testing strategies (annual colonoscopic surveillance, no testing age limit) compared with no testing ranged from 28 915 to 31 904/life‐year saved (LYS) (indicative willingness‐to‐pay threshold: 30 000–50 000/LYS). These strategies could avert 184–189 CRC deaths with an additional 30 597–31 084 colonoscopies over the lifetimes of 1000 patients with incident CRC with LS and 1420 confirmed LS carrier relatives (164–166 additional colonoscopies/death averted). The most cost‐effective strategy was immunohistochemistry and BRAF V600E testing (incremental cost‐effectiveness ratio [ICER], 28 915/LYS). Universal germline gene panel testing was not cost‐effective compared with universal tumour testing strategies (ICER, 2.4 million/LYS). Immunohistochemistry and BRAF V600E testing was cost‐effective at all age limits when paired with 2‐yearly colonoscopic surveillance (ICER, 11 525–32 153/LYS), and required 4778–15 860 additional colonoscopies to avert 46–181 CRC deaths (88–103 additional colonoscopies/death averted). Conclusions: Universal tumour testing strategies for guiding germline genetic testing of people with incident CRC for LS in Australia are likely to be cost‐effective compared with no testing. Universal germline gene panel testing would not currently be cost‐effective.